1999
DOI: 10.1080/08964289909596740
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Course of Disease in Multiple Sclerosis

Abstract: In this prospective study, 96 healthy controls and 101 multiple sclerosis patients were followed up for as many as 6 years, and self-reported stressful events and health status were assessed. The authors evaluated (a) whether patients reported more stressful life events than healthy controls and (b) the bidirectional relationship between stress and functional deterioration among patients. Healthy controls reported more life events than patients, Odds ratio (OR) = 1.13, p < .0001; and this relationship was attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 24 publications
1
36
1
2
Order By: Relevance
“…They also found that stress levels increased over time among those without effective coping strategies (Brown et al., 2006). However, in a second study that compared stressful events and health status between MS patients and healthy controls during a 6‐year follow‐up, healthy controls actually reported more stressful events than patients (although this finding may have been influenced by the fact that healthy controls may have had more interactions in life activities putting them at greater risk for negative events) (Schwartz et al., 1999). The risk of disease progression in MS patients increases with increasing stress, leading to the development of a vicious cycle where stress precipitates disease progression, which in turn increases stress, which causes further disease progression, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that stress levels increased over time among those without effective coping strategies (Brown et al., 2006). However, in a second study that compared stressful events and health status between MS patients and healthy controls during a 6‐year follow‐up, healthy controls actually reported more stressful events than patients (although this finding may have been influenced by the fact that healthy controls may have had more interactions in life activities putting them at greater risk for negative events) (Schwartz et al., 1999). The risk of disease progression in MS patients increases with increasing stress, leading to the development of a vicious cycle where stress precipitates disease progression, which in turn increases stress, which causes further disease progression, and so forth.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for MS patients, investigating negative interactions is particularly important as it is suggested that stress (e.g. negative interactions) is related to periods of disease activity in MS (Schwartz et al, 1999).…”
Section: Article In Pressmentioning
confidence: 99%
“…Perceptions regarding the uncertainty in disease, intrusiveness in daily activities, and lack of hope have been associated with depression [13]. Life stress and coping abilities may also mediate psychosocial outcomes [14].…”
Section: Psychosocial Effects Of Multiple Sclerosismentioning
confidence: 99%